Is the Glass Half Empty Or Half Full? : Issues in Managing Water Challenges and Policy Instruments - Kochhar, Kalpana (Staff Discussion Notes; Staff Discussion Notes, 2015)
This paper examines water challenges, a growing global concern with adverse economic and social consequences, and discusses economic policy instruments. Water subsidies provided through public utilities are estimated at about USD 456 billion or 0.6 percent of global GDP in 2012. The paper suggests that getting economic incentives right, notably by reforming water pricing, can go a long way towards encouraging more efficient water use and supporting needed investment, while enabling policies that protect the poor. It also discusses pricing reform options and emphasizes an integrated and holistic approach to manage water, going beyond the water sector itself. The IMF can play a helpful role in ensuring that macroeconomic policies are conducive to sound water management.